Beitrag zur Unterwasserbildrestauration - Stephan, Thomas (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2017)
Underwater images are most often degraded by color shifts, blurring and brightening effects. The presented approach is based on a problem-specific physical model of under water image formation. Thereon, methods of image restoration and image data retrieval are presented, which invert image degradation processes. Hence, it is possible to enhance image quality with model knowledge under different image acquisition conditions.